The poverty reduction strategy of the government of Brazil: A rapid appraisal - José Márcio Camargo; Francisco de Hollanda Guimar\~aes Ferreira (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2000)
This paper provides an overview of both the current structure of poverty in Brazil through a detailed poverty profile and of the aggregate dynamics of poverty in the last two decades. We then assess a number of government policies and programs which are either specifically designed to reduce poverty or have a direct bearing on current or future social welfare. A brief discussion of the Comunidade Solidária Programme is followed by an analysis of the coverage and targeting performance of mainstream programs in the areas of education, health, social security and other transfers. Our main findings are that a fifth of the Brazilian population live in indigence, and that this does not represent a substantial improvement over the situation two decades ago. A share of the blame for this must be borne by the highly regressive pattern of incidence of `social expenditures' which are, on the whole, disproportionately appropriated by the middle-classes and the rich.
Keywords: I31; I32; 330